2021
DOI: 10.1016/j.jbc.2021.100336
|View full text |Cite
|
Sign up to set email alerts
|

Maturation, inactivation, and recovery mechanisms of soluble guanylyl cyclase

Abstract: Soluble guanylate cyclase (sGC) is a heme-containing heterodimeric enzyme that generates many molecules of cGMP in response to its ligand nitric oxide (NO); sGC thereby acts as an amplifier in NO-driven biological signaling cascades. Because sGC helps regulate the cardiovascular, neuronal, and gastrointestinal systems through its cGMP production, boosting sGC activity and preventing or reversing sGC inactivation are important therapeutic and pharmacologic goals. Work over the last two decades is uncovering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 128 publications
(186 reference statements)
2
27
0
Order By: Relevance
“…GAPDH can bind heme from intracellular sources (acquired heme) 31 or bind the heme synthesized in the mitochondria. Heme bound to GAPDH constitutes the labile heme pool, 50,51 and this can be used to deliver heme to downstream target proteins to enable their heme‐maturations 35,52 . The Mb and Hb heme‐maturation processes also require an active sGCα1β1 heterodimer making cGMP and this induction maybe translational or transcriptional 27,37,40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GAPDH can bind heme from intracellular sources (acquired heme) 31 or bind the heme synthesized in the mitochondria. Heme bound to GAPDH constitutes the labile heme pool, 50,51 and this can be used to deliver heme to downstream target proteins to enable their heme‐maturations 35,52 . The Mb and Hb heme‐maturation processes also require an active sGCα1β1 heterodimer making cGMP and this induction maybe translational or transcriptional 27,37,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Heme bound to GAPDH constitutes the labile heme pool, 50,51 and this can be used to deliver heme to downstream target proteins to enable their heme-maturations. 35,52 The Mb and Hb heme-maturation processes also require an active sGCα1β1 heterodimer making cGMP and this induction maybe translational or transcriptional. 27,37,40 GAPDH itself can deliver heme to sGCβ1 32 and thus can regulate these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes protein structural changes that activate cGMP production ( 13 16 ). The essential role that heme plays in sensing NO underscores the importance of the heme delivery and insertion steps that enable sGC to mature in cells ( 17 ). Our recent studies have illuminated parts of the sGC maturation process: After translation, the immature sGCβ subunit is heme-free and accumulates in cells in the form of a complex with the cell chaperone hsp90 ( 18 , 19 ).…”
mentioning
confidence: 99%
“…The current work reveals that the association of an activator compound (heme- and NO-independent) with the sGC enzyme can be modulated reversibly by heme's redox status. In recent years, it has been shown that the sGC dimer enzyme does not exist in cells and tissues all in a heme-associated or a heme-devoid form, but these two functionally distinct forms coexist and their presence constantly reflects the cellular environment ( Stasch et al., 2006 , Stuehr et al., 2021 ; Sandner et al., 2021 , Ghosh & Stuehr, 2017 ).…”
Section: Discussionmentioning
confidence: 99%